A comparative analysis of Indonesian and Singaporean mathematics textbooks on the topic of polyhedrons - Ramadan, Dwi Cahya; Susanti, Ely; Martin, Cecil Hiltri (Cakrawala, 2025)
This study aims to conduct a comparative analysis of three mathematics textbooks on the topic of Polyhedrons, namely two textbooks from Indonesia (KTSP 2006 and Kurikulum Merdeka 2022) and one textbook from Singapore (New Syllabus Mathematics 2018). The method used is descriptive comparative with document analysis techniques. The focus of the study includes the presentation of facts, concepts, and principles, as well as question analysis based on Bloom’s Taxonomy cognitive levels, alignment with the PISA framework, and problem-solving components. The results indicate that the Kurikulum Merdeka textbook stands out in its variety of cognitive levels (C1–C6) and integration of PISA-type questions. The KTSP textbook follows a more deductive approach and lacks higher-order thinking questions, while the Singaporean textbook balances inductive and deductive approaches but only covers C3–C4 levels. All three textbooks include problem-solving tasks with varying levels of complexity. These findings offer insights for the development of more effective and context-based mathematics textbooks.